Almon Ferdinand Rockwell papers - Rockwell, Almon Ferdinand, 1835-
Correspondence, diaries, journals, reports, and other papers relating principally to the presidential administration and assassination of James A. Garfield. Correspondence with Garfield relates to their friendship, investments in the Silver King Mining Company, controversy over the resignation of New York senator Roscoe Conkling, and Garfield's appointment of Rockwell as superintendent of public buildings in Washington, D.C. Rockwell's diaries describe his Civil War service as an aide to Gen. Don Carlos Buell; the federal occupation of Nashville, Tenn.; battles of Shiloh and Corinth, Miss.; campaigns in northern Alabama; the pursuit of Confederate Gen. Braxton Bragg in Kentucky; the death of Gen. William Nelson; and Buell's removal and reinstatement in the U.S. Army. Also includes reports of Rockwell's conversation with Garfield shortly before the latter's death and a letter describing the death of Abraham Lincoln at which Rockwell was also present. Other correspondents include James M. Barney, Don Carlos Buell, Frank Abial Flower, Charles F. Manderson, William Henry Seward, and John M. Wilson.
Library of Congress Prints and Photographs Division.
Army officer and superintendent of public buildings, Washington, D.C.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barney, James M. -- Correspondence; Bragg, Braxton, -- 1817-1876.; Buell, Don Carlos, -- 1818-1898 -- Correspondence; Conkling, Roscoe, -- 1829-1888.; Flower, Frank Abial, -- 1854-1911 -- Correspondence; Garfield, James A. -- 1831-1881.; Garfield, James A. -- 1831-1881 -- Assassination; Garfield, James A. -- 1831-1881 -- Correspondence; Garfield, James A. -- 1831-1881 -- Death and burial; Lincoln, Abraham, -- 1809-1865 -- Death and burial; Manderson, Charles F. -- 1837-1911 -- Correspondence; Nelson, William, -- 1824-1862.; Seward, William Henry, -- 1801-1872 -- Correspondence; Wilson, John M. -- 1837-1919 -- Correspondence; Silver King Mining Company; Corinth, Battle of, Corinth, Miss., 1862.; Public buildings -- Washington (D.C.); Shiloh, Battle of, Tenn., 1862.; Silver mines and mining; Alabama -- History -- Civil War, 1861-1865.; Kentucky -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865.; Nashville (Tenn.) -- History -- Civil War, 1861-1865.; New York (State) -- Politics and government -- 1865-1950.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- Politics and government -- 1877-1881.; Army officers; Public officials